Circulating CD34+ Progenitor Cells and Risk of Mortality in a Population With Coronary Artery Disease. Issue 2 (16th January 2015) - Patel, Riyaz S.; Li, Qunna; Ghasemzadeh, Nima; Eapen, Danny J.; Moss, Lauren D.; Janjua, A. Umair; Manocha, Pankaj; Al Kassem, Hatem; Veledar, Emir; Samady, Habib; Taylor, W. Robert; Zafari, A. Maziar; et al.
<x xml:space="preserve">Abstract</x> Rationale: Low circulating progenitor cell numbers and activity may reflect impaired intrinsic regenerative/reparative potential, but it remains uncertain whether this translates into a worse prognosis. Objectives: To investigate whether low numbers of progenitor cells associate with a greater risk of mortality in a population at high cardiovascular risk. Methods and Results: Patients undergoing coronary angiography were recruited into 2 cohorts (1, n=502 and 2, n=403) over separate time periods. Progenitor cells were enumerated by flow cytometry as CD45med+ blood mononuclear cells expressing CD34, with additional quantification of subsets coexpressing CD133, vascular endothelial growth factor receptor 2, and chemokine (C-X-C motif) receptor 4. Coefficient of variation for CD34 cells was 2.9% and 4.8%, 21.6% and 6.5% for the respective subsets. Each cohort was followed for a mean of 2.7 and 1.2 years, respectively, for the primary end point of all-cause death. There was an inverse association between CD34+ and CD34+/CD133+ cell counts and risk of death in cohort 1 (β=−0.92, P=0.043 and β=−1.64, P=0.019, respectively) that was confirmed in cohort 2 (β=−1.25, P=0.020 and β=−1.81, P=0.015, respectively). Covariate-adjusted hazard ratios in the pooled cohort (n=905) were 3.54 (1.67–7.50) and 2.46 (1.18–5.13), respectively. CD34+/CD133+ cell counts improved risk prediction metrics beyond standard risk factors. Conclusions: Reduced circulating progenitor cell counts, identified primarily as CD34+ mononuclear cells or its subset expressing CD133, are associated with risk of death in individuals with coronary artery disease, suggesting that impaired endogenous regenerative capacity is associated with increased mortality. These findings have implications for biological understanding, risk prediction, and cell selection for cell-based therapies.